2013
DOI: 10.1680/nme.13.00024
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of polymers by graphene

Abstract: IntroductionDue to the rapid development of nanoscience and nanotechnology in the past 20 years, improvement of polymer properties by nanofillers has become a vital topic in the field of material science. [1][2][3] The polymer nanocomposites show enhanced properties by the incorporation of low amount of nanofillers such as carbon black (CB), carbon nanotubes (CNTs), graphene and nanoclay. [4][5][6][7] Due to the high surface to volume ratio and/or high aspect ratio, the nanofillers are more efficient than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…According to Equation (7), the critical pressure P c (d) increases with increasing d, reaches a maximum at d = √ 5/3β ≈ 0.57 nm, and then decreases. Asymptotically, P c (d) ∼ 24D/d 3 , which is what continuous-mechanics predicts for a thin-wall elastic ring (Lévy-Carrier law) [51].…”
Section: Collapse Of Nanotubesmentioning
confidence: 56%
See 1 more Smart Citation
“…According to Equation (7), the critical pressure P c (d) increases with increasing d, reaches a maximum at d = √ 5/3β ≈ 0.57 nm, and then decreases. Asymptotically, P c (d) ∼ 24D/d 3 , which is what continuous-mechanics predicts for a thin-wall elastic ring (Lévy-Carrier law) [51].…”
Section: Collapse Of Nanotubesmentioning
confidence: 56%
“…Besides its many potential applications [1], including the improvement of polymer properties and those of other host materials [2,3], graphene is an interesting model material for testing the prediction of two-dimensional (2D) mechanics [4]. In linear elasticity, the simplest formulation of the elastic energy of a 2D medium is the surface integral (1) involving the elements of the 2 × 2 strain tensor and the 2 × 2 curvature tensor κ.…”
Section: Introductionmentioning
confidence: 99%
“…This significant enhancement in elongation at break is attributed to the uniform dispersion of GO, strong interfacial interaction between GO and epoxy and reduction of epoxy crosslink density. However, at higher GO loading, the strong interactions between the GO sheet and epoxy matrix leads to diminishing epoxy molecular mobility and slightly reduces the elongation at break .…”
Section: Resultsmentioning
confidence: 99%
“…Although GO has good interfacial interaction with PK due to the oxygen functional groups in GO, since HA-GO and HP-GO contain additional surface functional groups, larger interfacial interactions between HA-GO or HP-GO and the PK matrix could be expected. Similarly, it was reported that when GO derivatives containing organic functional groups that have a specific interaction with the polymer matrix were used as fillers for polymer composites, they could increase the toughness of polymers [14,46].…”
Section: Mechanical Propertiesmentioning
confidence: 92%
“…Although the content difference of the organic moieties between HA-GO and HP-GO is only 1 wt.%, the mechanical strength values of HP-GO/PK are quite larger than those of HA-GO/PK because HP-GO contains larger content of rigid conjugated carbon units; more oxygen functional groups in HP-GO could be reduced because HP-GO is prepared using a longer reaction time (3 days) than HA-GO (12 h). Others also reported that the polymer composites containing more oxidized GOs have the smaller mechanical strength values [45][46][47]. Therefore, the carbon nanomaterials can increase the mechanical strength of the PK, while CNT, GO, and HP-GO having a relatively larger content of rigid conjugated carbon units are more effective than HA-GO in increasing the mechanical strength of PK.…”
Section: Mechanical Propertiesmentioning
confidence: 99%